STUDIES ON GENETIC VARIABILITY, HERITABILITY AND GENETIC ADVANCE IN AFRICAN MARIGOLD ( AN MARIGOLD (Tagetes erecta agetes erecta agetes erecta L.) - JITENDRA KUMAR SAHU; GAURAV SHARMA; S. K. NAIR; RAM SINGH (The Bioscan, 2018)
ABSTRACT The present investigation on variability, heritability and genetic advance in seventeen African marigold genotypes was carried out for plant growth and flower yield. The vegetative and flowering characters varied significantly among the genotypes. The highest value of GCV and PCV was observed for dry flower weight per plant (37.0% and 37.46%, respectively). High heritability was observed for xanthophyll content (99.9%), followed by dry flower weight per plant (97.53%). Plant height (95.0%), number of leaves per plant (94.8%).The estimates of genetic advance were comparatively maximum for number of leaves per plant (80.71%) followed by plant height (39.67%). For all the parameters, the estimates of phenotypic coefficient of variance (PCV) was higher as compared to genotypic coefficient variance (GCV), indicating the role of environmental factors for the expression of these characters. This suggests the presence of sufficient genetic variability can be exploited by practicing pure line selection